Legal realities of the Golden Horde Crimea through the eyes of foreign contemporaries - Roman Pochekaev (Крымское историческое обозрение)
The article is an analysis of specific status of the Crimea as a part of the Golden Horde and as it was reflected in the contemporary sources: notes of travelers, diplomats, merchants, missionaries, etc., correspondence of rulers, historical chronicles and hagiographic works based the information of eye-witnesses. Despite of the fact that the Crimean Peninsula was an integral part of the Golden Horde, its specific position, including the structure of population, international trade relations and the interest of the foreign states, caused the series of specific features in the legal regulations of different groups of inhabitants. The system of authorities in Crimea, taking into account the position of some cities (such as Sudak or Caffa), is observed as well as religious policy of khans towards different confessions, specific taxes and duties. The author finds out that although the Crimean Peninsula was completely in the field of the Golden Horde political and legal regulations, khans needed to take into consideration its strategic position, national and confessional structure of the population and these peculiarities were reflected in the Crimean legal realities.